Аналіз господарських випробовувань котка-подрібнювача рослинних решток соняшника - Богатирьов, Д. В.; Сало, В. М.; Bohatyrov, Dmitry; Salo, Vasily (КНТУ, 2013)
Напрям розробки та удосконалення сільськогосподарських машин для подрібнення рослинних решток в Україні є маловивченим але дуже актуальним. Представлено аналіз результатів польових випробовувань котка-подрібнювача вітчизняного. Основним показником роботи даної машини обрано співвідношення розмірів решток стебел соняшника після подрібнення. Наведені результати випробовувань свідчать про доцільність використання даного типу сільськогосподарської техніки. Agrarian economy of Ukraine and the global trend of environmentally friendly crop production leads to the search for new technologies of crop growing and developing the necessary technology. The need for fertilizers feed plants is always topical issue. Over the past decade, making huge quantities of mineral fertilizers significantly degrade the organic component of topsoil . Also, use of chemicals in agriculture leads to environmental pollution. There are many cases where fertilizers and other chemicals made ill-conceived and sometimes irresponsible. This leads to the accumulation of chemicals in soil, groundwater, excessive content of their crop production , and a food - and food of animal origin. This man-made pollution of fertile soil affects the quality of agricultural products , which can lead to increased morbidity. Widespread use of pesticides has created and specific problems associated with the acquisition of weeds, pests and pathogens resistance to them. Direction of development of agricultural machinery for crushing plant residues in Ukraine is a little known but very important. The analysis of the results of field testing of the roller-crusher. The main indicator of this unit size selected residues of sunflower stalks after shredding. The results of the tests indicate the feasibility of using this type of agricultural machinery.
Analysis of field trials roller-shredder residues of sunflower stalks
Keywords: коток-подрібнювач; стебла; довжина; рослинні рештки; roller-crusher; stems; length; cropresidues